UKURAN KANTOR AKUNTAN PUBLIK SEBAGAI PEMODERASI PENGARUH AUDITOR SWITCHING PADA KUALITAS AUDIT - Arestantya, Ida Ayu Radha; Wirajaya, I Gde Ary (E-Jurnal Akuntansi, 2016)
This study aimed to determine the effect size of the public accounting firm in the moderating effect of switching auditors on audit quality. The population used in this research is manufacturing companies listed on the Stock Exchange in 2012-2014 as many as 121 companies. Determination of the sample using purposive sampling technique with a sample of 81 observations. The analysis technique used is regression moderation / Moderated Regression Analysis (MRA). Based on the results of analysis show that the auditor switching positive effect on audit quality and reinforce the firm size effect of switching auditors on audit quality. The influence of the independent variable on the dependent variable is equal to 74.7 percent and the remaining 25.3 percent is influenced by other variables outside the model.
Keywords: Quality Audit; Auditor Switching; Size Public Accounting Firm (KAP)